1997
DOI: 10.1002/(sici)1097-0215(19970127)70:3<335::aid-ijc15>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

CPT‐11 in human colon‐cancer cell lines and xenografts: Characterization of cellular sensitivity determinants

Abstract: CPT-11, a new semisynthetic derivative of camptothecin, is active in a number of tumor types in the clinic, including colon cancer. CPT-11 is a drug that is converted into the active metabolite SN-38 by a carboxylesterase. Experiments were performed to obtain more insight in the cellular characteristics in 5 unselected human colon-cancer cell lines that account for the differential sensitivity to CPT-11 and SN-38.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
20
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 0 publications
4
20
2
Order By: Relevance
“…In the panel of five unselected human colon cancer cell lines, we have indeed found a positive correlation between the DNA topoisomerase I activity and the sensitivity to carboxylesterase-activated CPT-l1 and to SN-38 (Jansen et al, 1997a). Goldwasser et al (1995) have demonstrated a positive correlation between camptothecin sensitivity and the amount of drug-stabilized cleavable complexes.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In the panel of five unselected human colon cancer cell lines, we have indeed found a positive correlation between the DNA topoisomerase I activity and the sensitivity to carboxylesterase-activated CPT-l1 and to SN-38 (Jansen et al, 1997a). Goldwasser et al (1995) have demonstrated a positive correlation between camptothecin sensitivity and the amount of drug-stabilized cleavable complexes.…”
Section: Discussionsupporting
confidence: 63%
“…In a previous study in five unselected human colon cancer cell lines, we also demonstrated a difference in efficacy between carboxylesterase-activated CPT-11 and SN-38 (Jansen et al, 1997a). Explanations may be that various nutrients in tissue culture medium might inhibit the activation of the enzyme or that the carboxylesterase extract from porcine liver is not a good substitute for the endogenous carboxylesterase converting CPT-11 in other species.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…[14][15][16][17] Other studies determining predictive markers of CPT-11 efficacy have been highly controversial. [18][19][20][21][22] In vitro studies in colon cancer cell lines have suggested that Topo I activity may be a potential determinant of CPT-11 sensitivity. 18,19 Saltz et al described a significant correlation between mRNA levels of Topo I and response to CPT-11 based treatment in a small group of patients with metastatic CRC.…”
mentioning
confidence: 99%
“…The collision of CPT-11-stabilized topo I-bridged DNA breaks, referred to as cleavable complexes, with moving replication forks leads to lasting single-strand breaks and to cell death. Since the activity of topo I is frequently higher in colorectal tumors than in the normal colonic tissue, it may confer tumor specificity of the CPT-11-mediated effects, 6 and a decrease of topo I activity may contribute to the resistance of tumor cells. 7 The response in vivo appears also to correspond to the amount of cleavable complexes.…”
mentioning
confidence: 99%